Disaster Warnings in Your Pocket: How Audiences Interpret Mobile Alerts for an Unfamiliar Hazard. (9th March 2016) - Bean, Hamilton; Liu, Brooke F.; Madden, Stephanie; Sutton, Jeannette; Wood, Michele M.; Mileti, Dennis S.
Abstract : This study investigates how people interpret Wireless Emergency Alerts (WEAs) and Twitter‐length messages ('tweets') delivered over mobile devices for an unfamiliar hazard. Specifically, through four ( N =  31) focus groups and 31 think‐out‐loud interviews, participants' understanding of, belief in and personalisation of WEAs and tweets were assessed for a mock improvised nuclear device detonation in a major U.S. metropolitan area. While participants offered a wide variety of interpretations, WEAs and tweets were often deemed confusing, difficult to believe and impersonal. Participants also consistently found WEAs and tweets to be fear inducing and uninformative. The findings compel improvements in the way that WEAs and tweets are currently written, as well as indicate future directions for applied risk and crisis communication theory development.